The Polanyi Paradigm and a Dynamic Analysis of Archaic States - Gledhill, John (1982)
KeiBi-relevant 200-213: Polanyi's Impact on Near Eastern Studies: Markets, Merchants, and Accumulation - The Old Assyrian Trade.